Preparation of rice hull activated carbon for the removal of selected pharmaceutical waste compounds in hospital effluent - Mukoko, T.; Mupa, M.; Guyo, Upenyu; Dziike, F. (Environmental and Analytical Toxicology, 2016)
The adsorbent (activated carbon) was prepared from rice hull obtained from communal farmers in Mutoko North (Zimbabwe) by chemical activation using phosphoric acid and was used in the adsorption of aspirin, paracetamol and ibuprofen from hospital effluent. Characterization of the rice hull activated carbon was carried out using the following methods: SEM, XRD, FT- IR. Physical properties such as iodine number, porosity, ash content, moisture content and volatile matter content were also determined. Iodine number was found to be 815.0 ± 2.52 mg/g. FT-IR analysis showed the presence of various functional groups such as C=O, C=C, –OH, and C-H on the surface of the adsorbent whereas SEM micrograph showed that the external surface of the rice hull activated carbon is full of regular cavities. XRD pattern showed broad peaks indicating that rice hull activated carbon produced has amorphous structure. The effect of adsorbent dose, contact time, initial concentration and pH was studied. Adsorption of aspirin fits the Freundlich isotherm, whereas ibuprofen and paracetamol fit the Langmuir isotherm. Kinetic studies showed that adsorption of ibuprofen, aspirin and paracetamol obey pseudo-second order kinetics. Aspirin, paracetamol and ibuprofen were detected in two hospital waste waters at the concentrations of 0.117 ±0.0058 mg/L, 0.100 mg/L and 0.010 ± 0.0006 mg/L respectively. The studies showed that pharmaceutical compounds studied can be removed from wastewater using rice hull derived activated carbon.